The Relationship Among Poverty, Economic Growth, and Inequality Revisited - Stevans, Lonnie K.; Sessions, David N. (Journal of Income Distribution®, 2008)
It has been shown in prior research that increased economic growth reduces poverty. Authors have also found that the effect of growth in Gross Domestic Product (GDP) on poverty growth has either diminished or remained unchanged over time, and economic expansion in the 1980s in the United States had no affect on poverty. Using a formal error-correction model, we find that increases in economic growth are significantly related to reductions in the poverty rate for all families. Specifically, GDP growth was found to have a more pronounced effect on poverty during the expansionary periods of the 1960s, 1970s, 1980s, 1990s, and 2000s. Other findings include identification of determinants of the dynamic behavior of poverty rates both in the yearto- year periods and over the long run.